1993
DOI: 10.1021/j100115a025
|View full text |Cite
|
Sign up to set email alerts
|

Laser photolysis studies of transient processes in the photoreduction of naphthalimides by aliphatic amines

Abstract: The photoreduction of N-phenyl-1,8-naphthalimide and N-phenyl-2,3-naphthalimide by aliphatic amines has been studied by laser flash photolysis with transient absorption and transient conductivity methods in different solvents. Analysis of transient time profiles establish for most systems the occurrence of a fast primary and a slower secondary reduction process. Primary reduction is ascribed to the reaction between a triplet naphthalimide and an amine, while secondary reduction is assigned to the reaction of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
51
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 11 publications
11
51
0
Order By: Relevance
“…Selected excitation of quinones before electron transfer from N,N ‐diethylaniline (DEA), triethylamine (TEA) and 1,4‐diazabicyclo[2.2.2]octane (DABCO) is therefore possible. The photoreduction of AQ and 1‐Cl (ClAQ) and 1,8‐Cl 2 (Cl 2 AQ) derivatives (13–18), other quinones (4,7) and related aromatic compounds (39–42) by amines have been the subject of several investigations. A complication arises because QH 2 , in contrast to other hydroquinones, is not stable in solution, and addition of oxygen to QH 2 causes a complete recovery into AQ (10,20).…”
Section: Introductionmentioning
confidence: 99%
“…Selected excitation of quinones before electron transfer from N,N ‐diethylaniline (DEA), triethylamine (TEA) and 1,4‐diazabicyclo[2.2.2]octane (DABCO) is therefore possible. The photoreduction of AQ and 1‐Cl (ClAQ) and 1,8‐Cl 2 (Cl 2 AQ) derivatives (13–18), other quinones (4,7) and related aromatic compounds (39–42) by amines have been the subject of several investigations. A complication arises because QH 2 , in contrast to other hydroquinones, is not stable in solution, and addition of oxygen to QH 2 causes a complete recovery into AQ (10,20).…”
Section: Introductionmentioning
confidence: 99%
“…For TEA in acetonitrile (40–42) or water (45), however, equilibrium 11 with efficient formation of the α‐aminoethyl radical ( • DH) is known from related systems.…”
Section: Discussionmentioning
confidence: 99%
“…Benzoquinones, because of their n,π transition, can be excited at 308 or 350 nm in relatively low concentration and are therefore accessible for spectroscopy in the presence of additives absorbing at 250–300 nm. The photoreduction of quinones (10–14,26–33) and related aromatic compounds (40–43) by amines, such as N,N ‐dialkylamines, triethylamine (TEA) or 1,4‐diazabicyclo[2.2.2]octane (DABCO), has been intensively studied. Fourier‐transform infrared spectroscopy of quinones provides access toward structural information.…”
Section: Introductionmentioning
confidence: 99%
“…Saito et al (23) reported that photoreduction of IIB can proceed through an intramolecular electron transfer from the monothioacetal group on the side chain to the triplet state of the 1,8‐naphthalene imide chromophore. Earlier, formation of a radical anion from a related NI (R: ‐Ph) has been observed by EPR during its irradiation in acetonitrile in the presence of aliphatic amines as electron donors (17). The lack of an EPR spectrum from the IIB radical anion in our system could be due to its inherent low stability and, possibly, its rapid quenching by traces of oxygen, which affords superoxide.…”
Section: Discussionmentioning
confidence: 99%
“…Laser flash photolysis studies revealed that on irradiation, NI and NDI compounds, including IA , participate in photoredox processes because on photoexcitation they abstract electrons from certain donors such as aliphatic amines, DABCO and DNA bases (9, 11–13, 17, 18). In the absence of other donors, the NDI triplet was quenched by NDI molecules in the ground state (9, 12, 13).…”
Section: Introductionmentioning
confidence: 99%